The prevalence and factors associated with the delay in the initiation of breastfeeding - A. M., Mahanum; Leong, Joyce Whye Sook; Abdul Rahman, Anita; Ching, Siew Mooi; A., Enoma (Auricle Technologies Pvt., 2015)
Advanced research using the latest technology confirms that breast milk is indeed far more superior compared to formula milk in either its ingredients or its psychological effect for both, mother and baby when practising breastfeeding. Aims: To determine the prevalence and factors associated with the delay in the initiation of breastfeeding. Method: This is a cross-sectional study; universal sampling method was used in this study. All postnatal mothers who delivered in Hospital Putrajaya, from 20 December 2010 until 31 January 2011 were approached and recruited in this study. The inclusion criterias were: all mothers who delivered in Hospital Putrajaya and babies who can be breastfed. The participants were asked to complete a set of self-administered questionnaire which was adapted from Radzniwan et al and Reassessment Tools for Breastfeeding Hospital Initiative with permission. Descriptive statistics (mean, range and standard deviation) was used to describe the sample. The Chi square test was used to determine the association between the dependent and independent variables. All the data collected were analyzed using the software Statistical Analysis Package for Social Sciences (SPSS for Window Version 17.0). A p value of less than 0.05 was considered as statistically significant. Result: From this study, the prevalence of the delay in initiation of breastfeeding is 55.7%. It is higher compared to the study by Dewey et al, It also shows that ethnicity, educational level and the age categories were associated with the delay in initiation of breastfeeding. Those of Malay ethnicity delayed initiation for about 52.8% from the Malay respondents Conclusion: The main factors that were directly associated with the delay in the initiation of breastfeeding were Malay ethnicity, age between 26 -30 years old, and those who have undergone caesarean section delivery. These target groups must be given priority in giving health education, physical and emotional support during antenatal, intranatal and post-delivery.